Analisis Pengendalian Kualitas Hasil Pengelasan Bengkel Welding HO & AO di PT. A Menggunakan Metode Six Sigma dan New Seven Tools - Amalliyah, Nurul; Nugraha, Isna (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT A is a state-owned maritime manufacturing company that produces ships. There are a number of workshops that support the production process, one of which is the HO & AO Welding Workshop. The problems that occur in the HO & AO Welding Workshop are 3 types of defects that are often found in Welding results in the form of Spatter, Undercut, and Pin hole. This study aims to improve quality and propose improvements that can be made to reduce defects in the HO & AO Welding workshop at PT. A. Therefore, it is necessary to carry out quality control with the Six Sigma method and New Seven Tools. Based on the results of the study, it is known that the DMAIC (Define, Measure, Analyze, Improve, Control) analysis with the results obtained through testing the quality of Welding products resulted in 548 failure units, a DPMO value of 49289 and then converted to a sigma level of 3.15 which indicates that the sigma level is at the average of the Indonesian industry. It can be explained that the possibility of damage is 49289 for a million production. And the main defect-causing factors have been successfully identified through the application of New Seven Tools which include human, material, method, machine, and environmental factors. Therefore, PT. A is advised to implement improvement recommendations to reduce product defects. Keywords: Defect, New Seven Tools, Quality, Six Sigma, Welding